2013
DOI: 10.4310/mrl.2013.v20.n3.a9
|View full text |Cite
|
Sign up to set email alerts
|

Kählerian three-manifold groups

Abstract: Abstract. We prove that if the fundamental group of an arbitrary three-manifoldnot necessarily closed, nor orientable -is a Kähler group, then it is either finite or the fundamental group of a closed orientable surface.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…As a consequence of our results we deduce the restrictions on quasiprojective 3-manifold groups obtained by the authors of [DPS,FrSu,Ko2] and the restrictions on good complexifications of 3-manifolds deduced in [To] (this is done in in Section 3.1.1). We also indicate, in Remark 3.12, how to deduce the classification of (closed) 3-manifold Kähler groups [DiSu,Ko1,BMS] using the techniques of Theorem 1.1, thus providing a unified treatment of known results.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…As a consequence of our results we deduce the restrictions on quasiprojective 3-manifold groups obtained by the authors of [DPS,FrSu,Ko2] and the restrictions on good complexifications of 3-manifolds deduced in [To] (this is done in in Section 3.1.1). We also indicate, in Remark 3.12, how to deduce the classification of (closed) 3-manifold Kähler groups [DiSu,Ko1,BMS] using the techniques of Theorem 1.1, thus providing a unified treatment of known results.…”
Section: Introductionsupporting
confidence: 66%
“…A group is called quasiprojective (respectively, Kähler) if it is the fundamental group of a smooth complex quasiprojective variety (respectively, compact Kähler manifold). Kähler and quasiprojective 3manifold groups have attracted much attention of late [DiSu,Ko1,BMS,DPS,FrSu,Ko2]. In this paper we characterize quasiprojective 3-manifold groups.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, if Σ g is a Riemann surface of genus g 2, then π 1 (Σ g × [0, 1]) is certainly a Kähler group. (Added in proof: motivated by Theorem 1.1, and the implicit question we raised here, Kotschick [28] has now shown that, in fact, the only infinite, 3-manifold groups which are also Kähler groups are the surface groups. )…”
Section: 2mentioning
confidence: 91%
“…to be a fundamental group of a smooth quasi-projective variety. For application of these and ideas from different ideas, not discussed here, to the problem of characterisation of quias-projective and quasi-Kahler groups (in particular the comparison with the fundamental groups of 3-manifolds) see: [133], [76], [77], [19], [10], [124], [91], [32] 3.6. Isolated non-normal crossings.…”
Section: Homology Of Abelian Covers Characteristic Varieties Determin...mentioning
confidence: 99%